2015
DOI: 10.1097/aog.0000000000001032
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Expanded Access to a Collaborative Midwifery and Laborist Model With Cesarean Delivery Rates

Abstract: Objective To examine the association between expanded access to collaborative midwifery and laborist services and cesarean delivery rates. Methods This was a prospective cohort study at a community hospital between 2005 and 2014. In 2011, privately insured women changed from a private practice model to one that included 24-hour midwifery and laborist coverage. Primary cesarean delivery rates among nulliparous, term, singleton, vertex women and vaginal birth after cesarean delivery (VBAC) rates among women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 11 publications
10
37
0
Order By: Relevance
“…Increasing access to interprofessional models of care for low-risk women could further lower the rate of cesarean births, including repeat cesarean delivery, in the United States. Previous studies of midwifery care models found that women cared for by midwives have lower cesarean rates, 7,24,35 and our study further validates these findings.…”
Section: Discussionsupporting
confidence: 89%
“…Increasing access to interprofessional models of care for low-risk women could further lower the rate of cesarean births, including repeat cesarean delivery, in the United States. Previous studies of midwifery care models found that women cared for by midwives have lower cesarean rates, 7,24,35 and our study further validates these findings.…”
Section: Discussionsupporting
confidence: 89%
“…11,12 More recently, work at a California community hospital demonstrated lower primary and repeat cesarean deliveries when women were cared for within a midwife-obstetrician laborist (shift-based) practice model compared to a traditional private practice model. 13,14 Along with our data, the results of these studies suggest obstetrical care provision may differ based on issues such as work schedule.…”
Section: Commentsupporting
confidence: 74%
“…12 More recent publications have focused on differences in outcomes with laborist compared to traditional private practice models. Several of these publications have demonstrated benefits of laborist models 2-4 , while others fail to demonstrate a difference in outcomes, and specifically cesarean delivery rates, with and without laborists. 6 Based on our findings, some of this heterogeneity of results may depend on the individual laborists hired.…”
Section: Commentmentioning
confidence: 99%
“…2-4 An ACOG Committee Opinion defines a laborist as an obstetrician-gynecologist who is employed by the hospital to manage laboring patients and attend to obstetric emergencies. 5 Given this definition, this reduction in cesarean delivery is plausible with the increased availability of the laborist, focused expertise in labor management, and potentially a greater objectivity in assessing the clinical scenario when not managing a private patient.…”
Section: Introductionmentioning
confidence: 99%